Resolving School Staffing Problems in Greece: A Strategic Management Approach - Alexopoulos, Nikolaos (Frontiers in Education, 2019)
Schooling constitutes one of the most fundamental means to social well-being, cultural advancement, and economic growth in a nation. In order for school units to be effective in this role, it is imperative for their teaching staff to be well-trained, skilled, and eager to perform their duties. In Greece, staffing in primary and secondary public education is performed at a central level by the Ministry of Education, whose utmost priority is to safeguard transparency in the selection process rather than select those candidates who would be most capable of improving the operation of the country's public schools (in terms of its pedagogical, teaching, and administrative functions). Since early January 2019, the Greek Ministry of Education has reviewed existing school staffing practices, sparking reactions among the education community and professional teachers' unions as well as fueling discussions in society. The aim of this study is to critically deliberate upon school staffing practices in Greece by perusing pertinent literature and legislation. In particular, through the strategic management approach, it shall investigate whether school staffing in Greek schools is consistent with current and future education requirements concerning teaching staff with adequate knowledge and skills, as well as proper attitudes and behaviors. The present study also aims at identifying the degree to which this system provides newly appointed teaching staff with professional support so as to ensure a smooth and productive incorporation into the school unit.